HFE gene mutations in patients with altered iron metabolism in argentina - Rossetti, M V; Méndez, M; Afonso, S; Gerez, E.; Batlle, A; Muñoz, A; Parera, V E (Cellular and Molecular Biology, 2009)
Hereditary Hemochromatosis (HH) is an iron overload syndrome caused by increased duodenal iron absorption, which leads to excesive iron deposition in parenchymal cells of the liver and mayor organs, causing cirrhosis, diabetes, cardiac failure, endocrine complications and arthritis. There are 6 types of HH related to mutations in the genes that encode proteins of iron metabolism. HH Type I is inherited as an autosomal recessive trait of mutations in HFE gene. We investigate the prevalence of C282Y, H63D and S65C mutations in 95 individuals (77 males, 18 females) bearing iron metabolism alterations to establish an early diagnosis of HH. Among this population, 58% carried mutations in the HFE gene (45 males, 10 females). H63D mutation was found in 32.6% of the subjects (29.5% in heterozygocity, 3.15% in homozygocity). S65C mutation was only detected in the heterozygous form (5.3% of the patients), 2 of them carried also H63D mutation. C282Y in heterozygocity was found in 15.8% of the individuals; but only 4.15% carried this mutation in homozygocity. Our findings are in agreement with the prevalence of the Mediterranean origin of most of our patients, where C282Y mutation is not as common as H63D mutation.